Recent Aspects of Non-Performing Loans - Tabakov, Pavel (Research Papers, 2024)
The study examines the current scientific approach of non-performing loans through the prism of the regulations and guidelines for their management implemented after the Global financial and economic crisis by the European Central Bank and European Banking Authority. The approach for preparation a strategy for managing non-performing exposures and an operational plan for achieving short-term qualitative targets is presented. The recent NPL management model, including the so-called “Three lines of defense” is examined. The classification of non-performing loans according to the guidelines of the European Banking Authority is described in detail, as well as the restructuring and impairment of credit exposures. There are also outlined the methodology for accounting of financial assets implemented with International Financial Reporting Standard 9 – Financial Instruments in 2018 and the main criteria for applying the Definition of default from 2021. The causes that led to the bankruptcies of large banks in the USA and Europe in 2023 have been pointed out. Through a comparative analysis, the dynamics of non-performing loans in the EU and Bulgaria have been studied.